Effect of the addition of inulin on the nutritional, physical and sensory parameters of bread - Jacira Antonia Brasil; Karina Correia da Silveira; Silvana Magalhães Salgado; Alda Verônica Souza Livera; Zelyta Pinheiro de Faro; Nonete Barbosa Guerra (Universidade de São Paulo, 2011)
The present work evaluated the effect of the addition of inulin on sensory, nutritional and physical parameters of white bread. Three formulations containing 0%, 6% and 10% of inulin were produced. Physical analyses of mass, volume, specific volume, density, centesimal composition, glycemic index (GI) and qualitative descriptive sensory analyses, were carried out. The reduction in bread volume seen with 10% inulin was higher than that reported in the literature. Bread weight did not differ statistically. There was an 85% reduction in fat content for bread with 6% inulin and 86% for bread containing 10% inulin. Glycemic index in bread containing 10% inulin was lower than bread with 6% inulin and equal to inulin-free bread. A level of 6% inulin added to bread was regarded to yield good sensory quality. O presente trabalho avaliou o efeito da adição de inulina sobre os parâmetros sensoriais, nutricionais e físicos do pão branco. Foram desenvolvidas três formulações contendo 0%, 6% e10% de inulina. Foram realizadas análises físicas de massa, volume, volume específico, densidade, composição centesimal, índice glicêmico (IG) e análise sensorial descritiva quantitativa. A redução do volume do pão contendo 10% de inulina foi maior que os dados da literatura. O peso do pão não diferiu estatisticamente. Houve uma redução de 85% do teor de gordura do pão com 6% de inulina e 86% para o pão com 10% de inulina. O índice glicêmico obtido no pão com 10% de inulina foi menor do que o com 6% de inulina e igual ao sem inulina. O pão adicionado de 6% de inulina foi tido como de boa qualidade sensorial.